2019
DOI: 10.1002/brb3.1482
|View full text |Cite
|
Sign up to set email alerts
|

Selective microstructural integrity impairments of the anterior corpus callosum are associated with cognitive deficits in obstructive sleep apnea

Abstract: BackgroundThere is some evidence that obstructive sleep apnea (OSA) patients have white matter integrity abnormality in the corpus callosum (CC). However, whether the CC subregions are differentially affected in OSA is largely unknown.MethodsTwenty patients with OSA and 24 well‐matched healthy controls were enrolled and underwent diffusion tensor imaging (DTI) and clinical and cognitive assessments. DTI tractography was used to reconstruct the CC which was divided into five subregions. Intergroup differences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 56 publications
3
28
2
Order By: Relevance
“…Furthermore, a recent study performed by Baril et al (2020) (N = 65) found that mild OSA was associated with widespread areas of lower diffusivity along the skeleton in the centre of white matter (WM) in projection, association, and commissural fibres but not the brainstem, as well as lower free-water fraction and no changes in fractional anisotropy (FA) or WM hyperintensity volume, while subjects with moderate to severe OSA showed lower axonal diffusivity in the corpus callosum (CC) [13]. A similar result has also been reported by Zhang et al (2019) (N = 44), where subjects with moderate-severe OSA exhibited significant lower FA and higher mean and radial diffusivity in the anterior CC [25]. Furthermore, Koo et al (2020) (N = 79, male only) found OSA to be associated with lower FA in the bilateral anterior thalamic radiations and the right uncinated fasciculus [26].…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…Furthermore, a recent study performed by Baril et al (2020) (N = 65) found that mild OSA was associated with widespread areas of lower diffusivity along the skeleton in the centre of white matter (WM) in projection, association, and commissural fibres but not the brainstem, as well as lower free-water fraction and no changes in fractional anisotropy (FA) or WM hyperintensity volume, while subjects with moderate to severe OSA showed lower axonal diffusivity in the corpus callosum (CC) [13]. A similar result has also been reported by Zhang et al (2019) (N = 44), where subjects with moderate-severe OSA exhibited significant lower FA and higher mean and radial diffusivity in the anterior CC [25]. Furthermore, Koo et al (2020) (N = 79, male only) found OSA to be associated with lower FA in the bilateral anterior thalamic radiations and the right uncinated fasciculus [26].…”
Section: Introductionsupporting
confidence: 69%
“…In this review, we have summarised recent findings on the association between OSA and brain structure, cognition, and the two most common neurodegenerative disorders, namely Alzheimer's dementia and Parkinson's disease. Overall, recent studies reported associations between OSA and grey and white matter alterations [3, 10-12, 20, 22-24], and changes in brain diffusion [13,25,26], as well as impaired cognition, specifically regarding memory [5,6,26,32], attention [5,7,8,30,31], and executive control [7,8]. Furthermore, subjects with OSA were found to have a higher risk of developing mild cognitive impairment (MCI) [5,27], Alzheimer's dementia [16,17,[39][40][41], and Parkinson's disease [47], and show shorter progression times between cognitively normal and MCI or MCI and Alzheimer's dementia [17].…”
Section: Discussionmentioning
confidence: 98%
“…A more heterogeneous portrait was found in middle‐aged adults with OSA (results are summarized in Table ) (Castronovo et al, ; Chen et al, ; Koo et al, ; Kumar et al, ; Kumar et al, ; Lee et al, ; Macey et al, ; Macey et al, ; Zhang et al, ). In fact, while decreased FA suggesting poor white matter integrity was repeatedly found in middle‐aged individuals with OSA, as would be predicted by ongoing neurodegenerative processes (Sexton et al, ), lower diffusivities (MD, RD, and AD) were reported more consistently than higher diffusivities.…”
Section: Introductionmentioning
confidence: 98%
“…Many neuro-imaging studies have been conducted to reveal the structural changes in the brain in OSA, the pathophysiology of which has not yet been fully elucidated [ 8 , 9 ]. One of the common aims of studies on neurological diseases is to examine anatomic and functional changes of the brain and to evaluate their relationship with the disruption in cognitive processes.…”
Section: Introductionmentioning
confidence: 99%